Analysis of the Implementation of Social Responsibility Accounting at PT. Pelabuhan Indonesia 1 (Persero) - Mulyani, Sri; Astuti, Citra; Aula, Muhammad Rizki; Amri, Syaiful (Universitas Dharmawangsa Medan, 2025)
This study aims to determine how social responsibility accounting is applied at PT. Pelabuhan Indonesia I (Persero). This research was conducted at PT. Pelabuhan Indonesia I (Persero) which is located at Jalan Krakatau Ujung No. 100 Medan. This type of research is descriptive research. Data collection techniques are carried out by documenting and interviewing. The data analysis technique used is the qualitative descriptive method. Samples in 2020-2024. Based on the results of the study, it can be obtained that PT. Pelabuhan Indonesia I (Persero) has implemented social responsibility accounting. In this case, the company has carried out various social activities in the environment and society in order to help with all the problems that exist in Indonesian society today. This is indicated by the existence of social assistance, education and so on. PT. Pelabuhan Indonesia I (Persero) has implemented social responsibility accounting for the environment and society to support harmonious relations with the environment and society. This is indicated by the existence of various institutions that were established to preserve the environment and for the welfare of the Indonesian people. Especially for the community around PT. Indonesian Port Company I (Persero).